A close encounter of the massive kind - Maíz Apellániz, Jesús (2017)
We have used (a) HST ACS imaging and STIS spectroscopy, (b) ground-basedPIONIER/VLT long-baseline interferometry, and (c) ground-basedspectroscopy from different instruments to study the orbit of theextreme multiple system HD 93 129 Aa,Ab, which is composed of (at least)two very massive stars in a long-period orbit with e>0.92 that willpass through periastron in 2017/2018. In several ways, the system is aneta Car precursor. Around the time of periastron passage the two verystrong winds will collide and generate an outburst of non-thermal hardX-ray emission without precedent in an O+O binary since astronomers havebeen able to observe above Earth's atmosphere. A coordinatedmultiwavelength monitoring in the next two years will enable abreakthrough understanding of the wind interactions in such extremeclose encounters. Furthermore, we have found evidence that HD 93 129 Aamay be a binary system itself. In that case, we could witness athree-body interaction that may yield a runaway star or a stellarcollision close to or shortly after the periastron passage. Either ofthose outcomes would be unprecedented, as they are predicted to below-frequency events in the Milky Way.